2010
DOI: 10.1002/mame.200900316
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide‐12/Functionalized Carbon Nanofiber Composites: Evaluation of Thermal and Mechanical Properties

Abstract: This work aims at improving the interfacial bonding between polyamide‐12 and CNFs. CNFs were oxidized and dispersed in polyamide‐12 giving rise to polymer nanocomposites. The oxidation caused an increase in the specific surface area and structural defects of the fibers, as indicated by surface area and Fourier‐transform Raman spectroscopy. The nanocomposites exhibited improved thermal and thermo‐oxidative stabilities. The oxidized nanofibers had marginal effect on the crystallinity and crystallization of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…Similar results were also reported by Sandler et al, Perrot et al, and Chatterjee et al for PA12/MWNT fibers with elongation at break ranging between 10 and 325%. Weakened polymer‐nanotube interface and inclusions creating defects in the polymer chains were identified as some of the main causes . In this work, CNT agglomerates and randomly aligned nanofillers were observed by TEM, even after 500% elongation [Figure (c)], confirming that they could act as imperfections and lead to lower strain‐to‐failure.…”
Section: Resultssupporting
confidence: 51%
“…Similar results were also reported by Sandler et al, Perrot et al, and Chatterjee et al for PA12/MWNT fibers with elongation at break ranging between 10 and 325%. Weakened polymer‐nanotube interface and inclusions creating defects in the polymer chains were identified as some of the main causes . In this work, CNT agglomerates and randomly aligned nanofillers were observed by TEM, even after 500% elongation [Figure (c)], confirming that they could act as imperfections and lead to lower strain‐to‐failure.…”
Section: Resultssupporting
confidence: 51%
“…The improvement of tensile properties has been obtained through laser sintering of PA12/carbon nanofiber composites . Recently, it has been reported that with carbon nanofibers in PA12 the thermal and thermo‐oxidative stabilities of the matrix could be improved along with the stiffness of the material . The composite of PA12 with a small amount of the functionalized expandable graphene caused a significant improvement in the tensile strength, elongation to break, impact energy, and the toughness of the polymer, although no significant improvement in Young's modulus was reported .…”
Section: Polyamide Nanocomposites Based On Carbon Nanofillersmentioning
confidence: 99%
“…The D and G bands, the important indexes for judging the material order, are attributed to the disorder induced and tangential mode peaks, respectively. 25 The intensity ratio of the D to G bands (I D /I G ) FIGURE 2. Raman spectrum of pristine graphite, GO, P(3HB-co-4HB), and composites.…”
Section: Multifractal Analysismentioning
confidence: 99%
“…The D and G bands, the important indexes for judging the material order, are attributed to the disorder induced and tangential mode peaks, respectively. 25 The intensity ratio of the D to G bands (I D /I G ) can be a measure of the amount of carbon defect sites (amorphous carbon or functionalized structure) relative to graphitic planes. 7 The I D /I G value of the pristine graphite is 0.17, whereas the I D /I G value of the GO platelets is 0.97, indicating that some carbon-carbon double bonds are damaged in the graphite oxidation and some sp 2 hybrid carbon atoms change to the sp 3 hybrid structure.…”
Section: Multifractal Analysismentioning
confidence: 99%